Consumer Attitude Towards Shellfish In The Greek Market: A Pilot Study - BATZIOS, CH.; ANGELIDIS, P.; MOUTOPOULOS, D.K.; ANASTASIADOU, CH.; CHRISOPOLITOU, V. (Mediterranean Marine Science, 2003)
During the last decade, the Greek shellfish industry has experienced significant changes affecting both the market demand and the availability of the end products. Although, shellfish and seafood in general have been promoted as healthy food by marketing boards and private seafood companies in many countries all over the world, no attention has been paid so far to analysing the Greek consumer’s purchasing behaviour and attitudes towards the shellfish market. This paper presents the results of the first survey in this field of research, which was carried out in northern Greece (area of Katerini and Greater Thessaloniki) from January to March 2002. A randomly selected sample of 400 consumers filled in a questionnaire, which covered basic marketing aspects of shellfish consumption such as choice, purchase, reasons for consuming shellfish, confidence in shellfish hygiene certification, media influence, etc. Data analysis includes descriptive statistics, as well as chi-square (― 2 ) tests (crosstabulation) to examine possible relations between consumers’ demographic and socio-economic characteristics and shellfish marketing aspects. Analyses of the results have shown that the majority of Greek consumers prefer the exploitable to cultured shellfish and in general do not eat shellfish often. They prefer the traditional fish shops for purchasing shellfish and consume them mainly in summer. The strongest reason to buy shellfish is their taste, while freshness is considered as the most important criterion when deciding to buy shellfish. Moreover, the vast majority of the consumers prefer a certification of quality, trust the confirmation provided by the veterinary authorities, but do not prefer ready-to-eat shellfish. Results revealed that consumers’ behaviour and attitudes vary considerably according to their demographic and socio-economic characteristics. The results of this study could prove to be helpful for decision makers towards a more rational planning of production and improvement of distributing roots, which in turn would improve product quality and promote shellfish consumption.